Immunological Role of IL-3, IL-5 and Some Inflammation Markers in a Sample of Iraqi Patients with Rheumatoid Arthritis - Salman, Shams A.; AL-Jumaily, Rakad M. Kh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Rheumatoid arthritis (RA) occurs through joint inflammation and affects approximately one in 200 adults worldwide, with women affected two to three times more frequently than men. The design of this study is to examine serum levels and changes in immunological markers in Iraqi patients with RA. To evaluate the advantages of clinical biomarkers of autoimmune disorderliness as well as changes in some immunological markers and clinical outcomes associated with Iraqi rheumatoid arthritis patients. Interleukins-3 and 5 (IL-3 and IL-5) were quantified by ELISA assay kits in the serum of 60 patients with RA disease (age range 20–60 years) and 30 age-matched healthy control groups. The BMI (body mass index), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), anti-cyclic citrullinated peptide (anti-CCP), and complete blood count (CBC) were also measured. The results of IL-3 and IL-5 (341.56 ±12.10 and 504.28 ±25.20) levels displayed a significant increase in RA patients compared to control (154.66 ±9.24 and 117.61 ±3.73). The levels of ESR and Ant-CCP (37.60 ±2.72 and 0.637 ±0.02) increased significantly in RA patients as compared to control (8.12 ±1.14 and 0.308 ±0.01). Similar results were observed (11.98 ±1.18) with CRP levels in RA patients. The results of CBC indicated a significant reduction in hemoglobin (HB) levels (12.42 ±0.34) in RA patients, and there were no differences between other CBC parameters compared to healthy controls. These findings suggest that it is possible to use IL-3 and IL-5 as biomarkers for RA diagnosis.